Pengukuran Efektifitas Implementasi ERP-SAP Pada Industri Teh Di PTPN IV - Irna Ekawati; Rizki Alfi; Lisa Nesti (Prosiding SISFOTEK, 2020)
Tea industry in West Sumatra and Jambi is under the auspices of PTPN VI which has a head office in Jambi City and has two production units namely Kayu Aro and Danau Kembar. Since 2018 PTPN VI has used one of the SAP software for the integration of its corporate information systems. This study aims to explore how the conditions of ERP implementation in PTPN VI, especially the tea industry which includes business processes, implementation stages, implementation constraints and how big the size of ERP implementation success in PTPN VI. The study was conducted at PTPN VI Headquarters and in both tea production units using interview techniques and questionnaire media to measure the success of implementation by developing the DeLone and McLean model that was processed with the Structural Equation Modeling approach. Measuring the success of implementation shows that the implementation was quite successful where information quality, system quality and service quality affect the level of usage and customer satisfaction which ultimately results in net benefits received.